Relevansi Filsafat Pendidikan Islam Di Era Digital Dan Artificial Intelligence - Firdaus, Restu Aditia; Sofy, Malik (Al-Wajih: The Journal of Islamic Studies, 2025)
The rapid development of digital technology and Artificial Intelligence (AI) has brought fundamental changes to educational systems and learning practices. While technological advancement offers efficiency, flexibility, and broader access to information, it also raises serious ethical and philosophical concerns, including moral degradation, academic dishonesty, and the reduction of education to mere technical skill acquisition. This article aims to examine the relevance of Islamic educational philosophy in addressing the challenges of education in the digital and AI era. This study employs a library research method with a descriptive-analytical approach by examining the ideas of prominent Islamic educational philosophers such as Al-Ghazali, Syed Muhammad Naquib al-Attas, and Ibn Khaldun. The findings indicate that Islamic educational philosophy, through the concepts of ta’lim, tarbiyah, and ta’dib, provides a comprehensive ethical and philosophical framework for guiding the responsible use of educational technology. By emphasizing adab and spiritual values as the core of education, Islamic educational philosophy remains highly relevant in shaping knowledgeable, ethical, and socially responsible individuals in the era of digital transformation.